Minkowski functional characterization and fractal analysis of surfaces of titanium nitride films. (12th June 2019) - Grayeli Korpi, Alireza; Ţălu, Ştefan; Bramowicz, Mirosław; Arman, Ali; Kulesza, Sławomir; Pszczolkowski, Bartosz; Jurečka, Stanislav; Mardani, Mohsen; Luna, Carlos; Balashabadi, Parvin; Rezaee, Sahar; Gopikishan, Sabavath
Abstract: The aim of this study is to gain a deeper understanding of the micromorphology characteristics of thin titanium nitride (TiN) films sputtered on glass substrates by using ion beam sputtering (IBS). For that purpose, TiN samples were deposited onto glass substrates from gas mixtures with different contents of molecular nitrogen and argon atoms. Atomic force microscopy (AFM) was used to characterize the surface microtexture of obtained thin films at high magnification. The detailed analysis of AFM images using Minkowski functionals and fractal analysis reveals a significant effect of the preparation conditions on the surface features with non-monotonic dependences. Presented results suggest that non-classical spatial characteristics of the variability of the surface topography, including fractal dimension, corner frequency, roughness, and feature shape and size, can be tuned having control over the relative flow rates of the gas mixture during film deposition.